2018
DOI: 10.1061/(asce)up.1943-5444.0000477
|View full text |Cite
|
Sign up to set email alerts
|

Intercity Passenger Rails: Facilitating the Spatial Spillover Effects of Population and Employment Growth in the United States, 2000–2010

Abstract: This research examines the association that intercity passenger rails have with population and employment growth at the county level in the continental United States from 2000 to 2010. This research adopts an integrated spatial regression approach that incorporates both spatial lag and spatial error dependence. The data come from the U.S. Census Bureau, the Bureau of Transportation Statistics, the Land Developability Index, and the National Atlas of the United States. Population and employment change are regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some of them have used a variety of approaches to study the influence of HSR construction from the viewpoint of population and employment growth, environmental impacts, spatial and temporal structural characteristics, and urban consumption. Kasu et al used an integrated spatial regression model based on spatial lags and spatial error correlation to study the relevance between intercity passenger rail and population growth and employment growth in the continental United States (Kasu and Chi, 2018). Hiramatsu studied cities in the high-speed rail route in Kyoto, Japan, and developed an interregional computational general equilibrium model based on the behavioral patterns of consumers and producers, which explained the impact of high-speed rail construction on the growth of population and employment in different cities (Hiramatsu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have used a variety of approaches to study the influence of HSR construction from the viewpoint of population and employment growth, environmental impacts, spatial and temporal structural characteristics, and urban consumption. Kasu et al used an integrated spatial regression model based on spatial lags and spatial error correlation to study the relevance between intercity passenger rail and population growth and employment growth in the continental United States (Kasu and Chi, 2018). Hiramatsu studied cities in the high-speed rail route in Kyoto, Japan, and developed an interregional computational general equilibrium model based on the behavioral patterns of consumers and producers, which explained the impact of high-speed rail construction on the growth of population and employment in different cities (Hiramatsu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although OLS with log transformation can be used to model skewed data, studies found that retransforming the log-scale dependent variable would introduce bias [ 17 19 ], thus bias correction could become necessary. But there is no single correct method to correct bias and some methods could be labor intensive [ 20 , 21 ]. To address non-normal distribution of fishing trip cost data, Das [ 11 ] and Kirkpatrick et al [ 22 ] used GLMs with trip-level and vessel-specific covariates to estimate and predict trip costs in the U.S. northeast and Atlantic commercial fisheries, respectively.…”
Section: Introductionmentioning
confidence: 99%